(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
A general one-dimensional velocity model was determined using the arrival times of P waves, and three models for seismic zones called Eje Cafetero, Tolima and Subduction, allowing thus a better location of seismic events found in the study area limited to the quadrant defined as longitude 76.7 ° W 74.5 ° W and latitude 4.0° N to 5.8° N. The events were provided by the National Seismic Network of Colombia (NSNC, Ingeominas), the Volcanological and Seismological Center of Manizales (CVSM) and the Seismological Observatory at University of Quindío (SOQ). Using the Wadati method, a relationship Vp/Vs=1.771 was determined. For the study zone, 3349 events were located using the software SEISAN and the non-linearized ray inversion method of VELEST . Welllocated events, with GAP <=250, RMS<=0.2 and errors in hypocenter and epicenter location smaller than 20 km, were selected. With the 1327 remaining events the velocity structure model were determined. The final result of the inversion shows velocity models of flat layers. For the shallow models, the depths are between 0 and 100 km; and for the Subduction model the depths range between 60 km and 205 km. The Moho (Mohorovicic discontinuity) for these models is located between 30km and 40 km approximately. The General model has a RMS of 0.064925 sec, the model for the seismic zone Tolima has a RMS of 0.064259 sec; the model for the seismic zone Eje Cafetero has a RMS of 0.0479s and the model for the seismic zone Subduction has a RMS 0.082256 seconds.